Oral health of elite athletes and association with performance: a systematic review - Ashley, P.; Di Iorio, A.; Cole, E.; Tanday, A.; Needleman, I. (British Journal of Sports Medicine, 2015)
Background: We aimed to systematically review the epidemiology of oral disease and trauma in the elite athlete population and to investigate the impact of oral health on sporting performance.